Auranofin, an Anti-rheumatic Gold Drug, Aggravates the Radiation-Induced Acute Intestinal Injury in Mice - Lee, Eun Sang; Kim, Joong Sun; Lee, Hyounji; Ryu, Jee-Yeon; Lee, Hae-June; Sonn, Jong Kyung; Lim, Young-Bin (Frontiers in Pharmacology, 2019)
Pelvic and abdominal radiotherapy plays an important role in eradication of malignant cells; however, it also results in slight intestinal injury. The apoptosis of cells in the intestinal epithelium is a primary pathological factor that initiates radiation-induced intestinal injury. Auranofin, a gold-containing triethylphosphine, was approved for the treatment of rheumatoid arthritis, and its therapeutic application has been expanded to a number of other diseases, such as parasitic infections, neurodegenerative disorders, AIDS, and bacterial infections. Recently, a treatment strategy combining the use of auranofin and ionizing radiation aimed at increasing the radiosensitivity of cancer cells was proposed for improving the control of local cancers. In this study, we evaluated the effect of auranofin on the radiosensitivity of intestinal epithelial cells. The treatment with a combination of auranofin and 5 Gy ionizing radiation showed clear additive effects on caspase 3 cleavage and apoptotic DNA fragmentation in IEC-6 cells, and auranofin administration significantly aggravated the radiation-induced intestinal injury in mice. Auranofin treatment also resulted in the activation of the unfolded protein response and in the inhibition of thioredoxin reductase, which is a key component of the cellular antioxidant system. Pre-treatment with N-acetyl cysteine, a well-known scavenger of reactive oxygen species, but not with a chemical chaperone, which inhibits endoplasmic reticulum stress and the ensuing unfolded protein response, significantly reduced the radiosensitizing effects of auranofin in the IEC-6 cells. In addition, transfection of IEC-6 cells with a small interfering RNA targeted against thioredoxin reductase significantly enhanced the radiosensitivity of these cells. These results suggest that auranofin-induced radiosensitization of intestinal epithelial cells is mediated through oxidative stress caused by the deregulation of thioredoxin redox system, and auranofin treatment can be an independent risk factor for the development of acute pelvic radiation disease.